Association between healthy food environment and metabolic syndrome, waist circumference, and systolic blood pressure in older adults in Southern Brazil - Souza, Bianca Bittencourt de; Quialheiro, Anna; Correa, Elizabeth Nappi; Rech, Cassiano Ricardo; Giehl, Maruí Weber Corseuil; d’Orsi, Eleonora (Frontiers in Aging, 2022)
The aim of this study was to establish the association between healthy food outlet proximity, metabolic syndrome (MS) and two of its components (waist circumference -WC and systolic blood pressure-SBP) in older adults (63 to 107 years old, median 73 years) living in Florianópolis, South Brazil, in 2013-2014. This is a cross-sectional analysis of the second wave of EpiFloripa Aging Cohort Study. Individual-level data on MS, WC, SBP, socio-demographic and health-related characteristics were collected from face-face interviews. The healthy food environment was assessed to presence of number and type establishment. After that, the older adults' residence was georeferenced, and by the Geographical Information System (GIS) software, the number of each type of establishment was counted in a 500m buffer around the older adults households. Multivariate linear regressions were used to test the association between the exposure to food outlet proximity and continuous outcomes (systolic blood pressure and waist circumference), and multiple logistic regression was used to the dichotomous outcome metabolic syndrome (yes/no). The study revealed that the greater frequency of supermarkets and restaurants in the neighborhood were associated with a lower chance of having MS. WC was lower in those individuals living in places with greater availability of greengrocers and restaurants. The research concluded that the number of establishments in the neighborhood is associated with cardiometabolic outcomes, and the chance of metabolic syndrome and elevated waist circumference is lower for older adults who lives in neighborhoods with more access to establishments that sell base products of a healthy diet.